A long afterglow luminescent material and its preparation method and application
By adjusting the content and type of M and N elements in the CaMxNyTiO3Pr material, combined with the solution method preparation and the method of doping calcium titanate with rare earth metal ions, the existing long-afterglow luminescent materials have solved the problem of poor chemical stability, short afterglow time and lack of red color. Regarding the problem of luminescent materials, the afterglow time, brightness and chemical stability of the materials have been extended.
Patent Information
- Application Number
- CN202211720948.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The chemical stability of existing long afterglow luminescent materials is poor, the afterglow time is short, the brightness is low, and the lack of red luminescent materials makes it difficult to meet the practical application needs.
Using the chemical formula of CaMxNyTiO3Pr, by adjusting the types and contents of M and N elements, especially when limiting 0.1≤x<0.3, 0.1≤y<0.3, the afterglow time and luminous brightness of the material are enhanced. The material is prepared through a solution method. Calcium titanate is doped with rare earth metal ions to form uniform crystals and improve doping efficiency.
The afterglow time of the long-afterglow luminescent material is significantly extended and the luminous brightness is improved. The material has good chemical stability, good water resistance, low cost, does not contain radioactive elements, and is safe and environmentally friendly.
Smart Images

Figure CN116179201B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solid luminescent materials, and its classification number is C09K11 / 67. Specifically, it relates to a long afterglow luminescent material and a preparation method and application thereof. Background Art
[0002] Long afterglow luminescent materials are energy storage materials that do not consume electricity. After being stimulated by light sources such as sunlight, they can store the absorbed natural light and still emit visible light when the light source is removed. Due to the physical and chemical properties of this type of material, it has been widely used in marking, construction, medicine and other fields.
[0003] Traditional afterglow materials are mostly alkaline earth metals or transition metal sulfides. These materials have poor chemical stability and require the addition of radioactive isotopes, which are extremely harmful to the environment. Subsequently, researchers developed long afterglow alkaline earth aluminate materials, but these materials are unstable when exposed to water and are not suitable for some water-based coatings. Moreover, their luminescent colors are mostly blue-green, and there is still a lack of red luminescent materials. In the titanate system, rare earth Pr 3+ The activated CaTiO3 has red luminescence characteristics, but the afterglow time does not meet the application requirements. In addition, CdSiO3 and MgSiO3 in the silicate system, although they have good chemical stability, have short afterglow time and low brightness.
[0004] Patent CN105647532A discloses a red long afterglow material and a preparation method thereof. The red long afterglow material is obtained by using CaTiO3 as a base material and adding zinc, praseodymium, aluminum and magnesium elements. The afterglow time is only 60 minutes, which is difficult to meet the actual application requirements.
[0005] Patent CN1810921A discloses a red long afterglow luminescent material and its preparation method, using MgZn2(PO4)2 as the matrix material and adding Mn 2+ and co-activating ion Tb 3+ The luminescent material prepared does not contain radioactive elements and has a low raw material cost, but its afterglow time is only up to 3 hours. Summary of the invention
[0006] In order to solve the above problems, the first aspect of the present invention provides a long afterglow luminescent material, the chemical formula of which is CaM x N y TiO3Pr.
[0007] Preferably, in the chemical formula of the long afterglow luminescent material, M is one or more elements of Sr, Ba, Mg, and Be, and N is one or more elements of Yb, Er, Nd, Tm, and Ho.
[0008] Further preferably, in the chemical formula of the long afterglow luminescent material, M is at least one of Sr and Ba, and N is at least one of Yb, Er and Nd.
[0009] Further preferably, in the chemical formula of the long afterglow luminescent material, M is Sr and N is Yb.
[0010] Preferably, in the formula, 0≤x<0.4, 0≤y<0.4.
[0011] Further preferably, 0.1≤x<0.3, 0.1≤y<0.3 in the formula. The applicant has found that when 0.1≤x<0.3, 0.1≤y<0.3 in the limiting formula, the afterglow time and the afterglow luminescence brightness are enhanced. It is speculated that the yttrium and strontium at this time can not only make the crystal of the material smaller, but also reduce the surface defects of the material, reduce the quenching effect of the afterglow luminescence, and also because of the structure of yttrium and strontium, they can interact with trivalent praseodymium ions or traps, thereby changing the distribution of traps and deepening the depth of trap energy levels. At the same time, it is easier for electrons to overcome the energy barrier between the trap energy level and the excited state, while extending the afterglow time, it also improves the afterglow luminescence brightness.
[0012] More preferably, in the formula, x is 0.2 and y is 0.2.
[0013] The second aspect of the present invention provides a method for preparing a long afterglow luminescent material, comprising the following steps:
[0014] (1) Ingredients: A calcium-based material is dissolved in deionized water to obtain a calcium-based solution, and a titanium-based material is dissolved in anhydrous ethanol to obtain a titanium-based solution. Thereafter, the titanium-based solution is added to the calcium-based solution under stirring at a speed of 400-600 rpm / min to obtain a first mixed solution. Thereafter, a praseodymium-based material, an M-based material, and an N-based material are dissolved in deionized water to obtain a second mixed solution. Thereafter, the second mixed solution is added to the first mixed solution under stirring at a speed of 400-600 rpm / min to obtain a mixed solution.
[0015] (2) Drying and grinding: The mixed solution is dried to obtain a calcium titanate-doped rare earth solid, which is then ground in a mortar for 1-2 hours to obtain a calcium titanate-doped rare earth powder;
[0016] (3) High temperature sintering: Calcium titanate doped rare earth powder is sintered at high temperature, quenched, and then cooled to 20-30°C to obtain the product.
[0017] Preferably, the molar ratio of the calcium-based material, titanium-based material, praseodymium-based material, M-based material and N-based material in the mixed solution is 1:1: (0.3%-1.4%): (0-0.4): (0-0.4). The applicant has found that when the molar ratio of the calcium-based material, titanium-based material, praseodymium-based material, strontium-based material and yttrium-based material in the mixed solution is limited to 1:1: (0.3%-1.4%): (0-0.4): (0-0.4), especially when the molar ratio of the calcium-based material and the praseodymium-based material is limited to (0.3%-1.4%), the afterglow luminescence time is enhanced, because the calcium source and the praseodymium source within this molar ratio form hole trap centers and electron trap centers, which increase the crystal defect concentration. At the same time, the concentration quenching effect will not occur due to the excessively high crystal defect concentration, thereby reducing the afterglow effect.
[0018] Further preferably, the molar ratio of the calcium-based material, the titanium-based material, the praseodymium-based material, the M-based material and the N-based material in the mixed solution is 1:1:(0.3%-0.8%):(0.1-0.3):(0.1-0.3).
[0019] Further preferably, the molar ratio of the calcium-based material, the titanium-based material, the praseodymium-based material, the M-based material and the N-based material in the mixed solution is 1:1:0.5%:0.2:0.2.
[0020] Preferably, the calcium-based material is selected from at least one of calcium chloride, calcium chlorate, calcium gluconate, calcium bicarbonate, calcium nitrate, calcium nitrate tetrahydrate, and calcium chloride hexahydrate; the titanium-based material is selected from at least one of tetrabutyl titanate, titanium tetrachloride, and titanyl sulfate; the praseodymium-based material is at least one of praseodymium nitrate, praseodymium chloride, and praseodymium acetate; the M-based material is acetate and / or nitrate; and the N-based material is acetate and / or nitrate.
[0021] Further preferably, the calcium-based material is selected from at least one of calcium nitrate tetrahydrate, calcium bicarbonate, and calcium gluconate, the titanium-based material is tetrabutyl titanate, the praseodymium-based material is praseodymium acetate and / or praseodymium nitrate, the M-based material is acetate, and the N-based material is acetate.
[0022] Further preferably, the calcium-based material is calcium nitrate tetrahydrate, the titanium-based material is tetrabutyl titanate, the praseodymium-based material is praseodymium acetate, the M-based material is strontium acetate, and the N-based material is yttrium acetate.
[0023] Preferably, the drying temperature in step 2 is 60-90° C. and the drying time is 30-40 hours.
[0024] Further preferably, the drying temperature in step 2 is 70-90° C. and the drying time is 35-40 hours.
[0025] Further preferably, the drying temperature in step 2 is 80° C. and the drying time is 36 hours.
[0026] Preferably, the specific steps of high temperature sintering in step 3 are: first heating the calcium titanate-doped rare earth powder at 20-30°C to 400-600°C at a rate of 3-6°C / min, reacting for 20-40min, then heating to 1100-1500°C at a rate of 2-5°C / min, and reacting for 2-5h.
[0027] Further preferably, the specific steps of high temperature sintering in step 3 are: first heating the calcium titanate-doped rare earth powder to 450-550°C at a rate of 4-6°C / min at 25°C, reacting for 25-35min, and then heating to 1200-1400°C at a rate of 2-4°C / min, and reacting for 2-4h.
[0028] Further preferably, the specific steps of high temperature sintering in step 3 are: first heating the calcium titanate-doped rare earth powder at 25°C to 500°C at a rate of 5°C / min, reacting for 30 minutes, and then heating to 1300°C at a rate of 3°C / min, and reacting for 3 hours.
[0029] Preferably, the specific cooling step in step 3 is: cooling to 20-30°C at a cooling rate of 2-5°C / min.
[0030] Further preferably, the specific cooling step in step 3 is: cooling to 25°C at a cooling rate of 2-4°C / min.
[0031] Further preferably, the specific cooling step in step 3 is: cooling to 25°C at a cooling rate of 3°C / min.
[0032] The third aspect of the present invention provides an application of a long afterglow luminescent material, which can be applied to road markings, tunnel inner walls, bridge guardrails, crash barriers, and traffic signs.
[0033] Beneficial effects:
[0034] (1) The present invention adopts a solution method to prepare a long afterglow material, so that the ions in the solution are evenly dispersed. At the same time, calcium titanate is doped with rare earth metal ions to make the crystal form more uniform and the doping efficiency higher. In addition, the compound doping elements strontium and yttrium make the material have a higher afterglow brightness and a more stable excitation wavelength under the irradiation of ultraviolet light, and the afterglow time of the material is greatly extended. The material can be used not only in road markings, tunnel inner walls, bridge guardrails, crash barriers, traffic signs, but also in LED lights, anti-counterfeiting coatings and other fields.
[0035] (2) The preparation method of the long afterglow material of the present invention is simple, has high repeatability and safety factor, and the product is evenly mixed. After the high-temperature roasting process, the color of the long afterglow material obtained is red and has very good water resistance, which solves the problem of less red luminescent materials in water-based coatings.
[0036] (3) The long afterglow luminescent material of the present invention has good chemical stability. The wavelength of the excitation light does not change when stored for too long. In addition, the material is safer during storage and transportation, and has low cost and can be mass-produced. The obtained product does not contain radioactive elements and will not cause harm to the environment and human body. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 : The crystal size of the long afterglow luminescent material prepared in Example 1 under a scanning electron microscope.
[0038] Figure 2 : The left picture shows the long afterglow luminescent material prepared in Comparative Example 1. The color of Comparative Example 1 under visible light is brown. The right picture shows that Comparative Example 1 (middle) fails to emit light after being irradiated with ultraviolet light (excitation wavelength is 365nm) for 5 minutes.
[0039] Figure 3 : The left picture shows the long afterglow luminescent materials prepared by Comparative Example 2 and Example 1. In the left picture, the luminescent brightness of Comparative Example 2 (left side) is lower after irradiation with ultraviolet lamp (excitation wavelength is 365nm) for 5 minutes, and the luminescent brightness of Example 1 (right side) is higher. In the right picture, the color of Comparative Example 2 (left side) under visible light is brown, and the color of Example 1 on the right side under visible light is light yellow.
[0040] Figure 4 : The left picture shows the long afterglow luminescent materials prepared by Comparative Example 3 and Example 1. In the left picture, the luminescent brightness of Comparative Example 3 (left and right) is low after irradiation with ultraviolet lamp (excitation wavelength is 365nm) for 5 minutes, and the luminescent brightness of Example 1 (middle) is high. In the right picture, the color of Comparative Example 2 (left and right) is brown under visible light, and the color of Example 1 (middle) is light yellow under visible light.
[0041] Figure 5 : The luminescence effect of the long afterglow material prepared in Example 1 dispersed in deionized water and immersed in ultraviolet light for 10 days (excitation wavelength is 365nm), and its luminescent color is red. Example
[0042] Example 1
[0043] A long afterglow luminescent material, the chemical formula of which is CaM x N yTiO3Pr, where M is Sr, N is Yb, x is 0.2, and y is 0.2.
[0044] This embodiment also provides a method for preparing a long afterglow luminescent material, comprising the following steps:
[0045] (1) Ingredients: The calcium-based material is dissolved in 10 g of deionized water to obtain a 0.59 g / mL calcium-based solution, and the titanium-based material is dissolved in 10 g of anhydrous ethanol to obtain a 0.85 g / mL titanium-based solution. Thereafter, the titanium-based solution is added to the calcium-based solution under stirring at a speed of 500 rpm / min to obtain a first mixed solution. Thereafter, the praseodymium-based material, the M-based material, and the N-based material are dissolved in 5 g of deionized water to obtain a second mixed solution. Thereafter, the second mixed solution is added to the first mixed solution under stirring at a speed of 600 rpm / min to obtain a mixed solution.
[0046] (2) Drying and grinding: The mixed solution was placed in an oven at 80° C. and dried for 36 h to obtain a calcium titanate-doped rare earth solid, which was then ground in a mortar for 1.5 h to obtain a calcium titanate-doped rare earth powder;
[0047] (3) High temperature sintering: The calcium titanate doped rare earth powder is first heated from 25°C to 500°C at a rate of 5°C / min, reacted for 30 minutes, then heated to 1300°C at a rate of 3°C / min, reacted for 3 hours, then quenched at 1000°C for 1 hour, and then cooled to 25°C at a cooling rate of 3°C / min.
[0048] The molar ratio of the calcium-based material, the titanium-based material, the praseodymium-based material, the M-based material and the N-based material in the mixed solution is 1:1:0.5%:0.2:0.2.
[0049] The calcium-based material is calcium nitrate tetrahydrate, the titanium-based material is tetrabutyl titanate, the praseodymium-based material is praseodymium acetate, the M-based material is strontium acetate, and the N-based material is yttrium acetate.
[0050] Example 2
[0051] A long afterglow luminescent material, the chemical formula of which is CaM x N y TiO3Pr, where M is Sr, N is Yb, x is 0.3, and y is 0.3.
[0052] This embodiment also provides a method for preparing a long afterglow luminescent material, comprising the following steps:
[0053] (1) Ingredients: The calcium-based material is dissolved in 10 g of deionized water to obtain a 0.59 g / mL calcium-based solution, and the titanium-based material is dissolved in 10 g of anhydrous ethanol to obtain a 0.85 g / mL titanium-based solution. Thereafter, the titanium-based solution is added to the calcium-based solution under stirring at a speed of 500 rpm / min to obtain a first mixed solution. Thereafter, the praseodymium-based material, the M-based material, and the N-based material are dissolved in 5 g of deionized water to obtain a second mixed solution. Thereafter, the second mixed solution is added to the first mixed solution under stirring at a speed of 600 rpm / min to obtain a mixed solution.
[0054] (2) Drying and grinding: The mixed solution was placed in an oven at 80° C. and dried for 36 h to obtain a calcium titanate-doped rare earth solid, which was then ground in a mortar for 1.5 h to obtain a calcium titanate-doped rare earth powder;
[0055] (3) High temperature sintering: The calcium titanate doped rare earth powder is first heated from 25°C to 500°C at a rate of 5°C / min, reacted for 30 minutes, then heated to 1300°C at a rate of 3°C / min, reacted for 3 hours, then quenched at 1000°C for 1 hour, and then cooled to 25°C at a cooling rate of 3°C / min.
[0056] The molar ratio of the calcium-based material, the titanium-based material, the praseodymium-based material, the M-based material and the N-based material in the mixed solution is 1:1:1.0%:0.3:0.3.
[0057] The calcium-based material is calcium nitrate tetrahydrate, the titanium-based material is tetrabutyl titanate, the praseodymium-based material is praseodymium acetate, the M-based material is strontium acetate, and the N-based material is yttrium acetate.
[0058] Example 3
[0059] A long afterglow luminescent material, the chemical formula of which is CaM x N y TiO3Pr, where M is Sr, N is Yb, x is 0.1, and y is 0.1.
[0060] This embodiment also provides a method for preparing a long afterglow luminescent material, comprising the following steps:
[0061] (1) Ingredients: The calcium-based material is dissolved in 10 g of deionized water to obtain a 0.59 g / mL calcium-based solution, and the titanium-based material is dissolved in 10 g of anhydrous ethanol to obtain a 0.85 g / mL titanium-based solution. Thereafter, the titanium-based solution is added to the calcium-based solution under stirring at a speed of 500 rpm / min to obtain a first mixed solution. Thereafter, the praseodymium-based material, the M-based material, and the N-based material are dissolved in 5 g of deionized water to obtain a second mixed solution. Thereafter, the second mixed solution is added to the first mixed solution under stirring at a speed of 600 rpm / min to obtain a mixed solution.
[0062] (2) Drying and grinding: The mixed solution was placed in an oven at 80° C. and dried for 36 h to obtain a calcium titanate-doped rare earth solid, which was then ground in a mortar for 1.5 h to obtain a calcium titanate-doped rare earth powder;
[0063] (3) High temperature sintering: The calcium titanate doped rare earth powder is first heated from 25°C to 500°C at a rate of 5°C / min, reacted for 30 minutes, then heated to 1300°C at a rate of 3°C / min, reacted for 3 hours, then quenched at 1000°C for 1 hour, and then cooled to 25°C at a cooling rate of 3°C / min.
[0064] The molar ratio of the calcium-based material, the titanium-based material, the praseodymium-based material, the M-based material and the N-based material in the mixed solution is 1:1:0.3%:0.1:0.1.
[0065] The calcium-based material is calcium nitrate tetrahydrate, the titanium-based material is tetrabutyl titanate, the praseodymium-based material is praseodymium acetate, the M-based material is strontium acetate, and the N-based material is yttrium acetate.
[0066] Comparative Example 1
[0067] The molar ratio of the calcium-based material, the titanium-based material, the praseodymium-based material, the M-based material and the N-based material in the mixed solution is changed to 1:1:0.2:0.2:0.2, and the rest is the same as in Example 1.
[0068] Comparative Example 2
[0069] The molar ratio of the calcium-based material, the titanium-based material, the praseodymium-based material, the M-based material and the N-based material in the mixed solution is changed to 1:1:1.5%:0.2:0.2, and the rest is the same as in Example 1.
[0070] Comparative Example 3
[0071] A long afterglow luminescent material, the chemical formula of which is CaM x N y TiO3, where M is La, N is Zn, x is 0.005, and y is 0.2.
[0072] This embodiment also provides a method for preparing a long afterglow luminescent material, comprising the following steps:
[0073] (1) Ingredients: The calcium-based material is dissolved in 10 g of deionized water to obtain a 0.59 g / mL calcium-based solution, and the titanium-based material is dissolved in 10 g of anhydrous ethanol to obtain a 0.85 g / mL titanium-based solution. Thereafter, the titanium-based solution is added to the calcium-based solution under stirring at a speed of 500 rpm / min to obtain a first mixed solution. Then, the M-based material and the N-based material are dissolved in 5 g of deionized water to obtain a second mixed solution. Thereafter, the second mixed solution is added to the first mixed solution under stirring at a speed of 600 rpm / min to obtain a mixed solution.
[0074] (2) Drying and grinding: The mixed solution was placed in an oven at 80° C. and dried for 36 h to obtain a calcium titanate-doped rare earth solid, which was then ground in a mortar for 1.5 h to obtain a calcium titanate-doped rare earth powder;
[0075] (3) High temperature sintering: The calcium titanate doped rare earth powder is first heated from 25°C to 500°C at a rate of 5°C / min, reacted for 30 minutes, then heated to 1300°C at a rate of 3°C / min, reacted for 3 hours, then quenched at 1000°C for 1 hour, and then cooled to 25°C at a cooling rate of 3°C / min.
[0076] The molar ratio of the calcium-based material, the titanium-based material, the M-based material and the N-based material in the mixed solution is 1:1:0.5%:0.2.
[0077] The calcium-based material is calcium nitrate tetrahydrate, the titanium-based material is tetrabutyl titanate, the M-based material is lanthanum acetate, and the N-based material is zinc nitrate hexahydrate.
[0078] Comparative Example 4
[0079] A long afterglow luminescent material, the chemical formula of which is CaM x N y TiO3Pr, where M=Sr, N=Yb, x is 0.5, and y is 0.6.
[0080] This embodiment also provides a method for preparing a long afterglow luminescent material, comprising the following steps:
[0081] (1) Ingredients: The calcium-based material is dissolved in 10 g of deionized water to obtain a calcium-based solution, and the titanium-based material is dissolved in 10 g of anhydrous ethanol to obtain a titanium-based solution. Thereafter, the titanium-based solution is added to the calcium-based solution under stirring at a speed of 500 rpm / min to obtain a first mixed solution. Thereafter, the praseodymium-based material, the M-based material, and the N-based material are dissolved in 5 g of deionized water to obtain a second mixed solution. Thereafter, the second mixed solution is added to the first mixed solution under stirring at a speed of 600 rpm / min to obtain a mixed solution.
[0082] (2) Drying and grinding: The mixed solution was placed in an oven at 80° C. and dried for 36 h to obtain a calcium titanate-doped rare earth solid, which was then ground in a mortar for 1.5 h to obtain a calcium titanate-doped rare earth powder;
[0083] (3) High temperature sintering: The calcium titanate doped rare earth powder is first heated from 25°C to 500°C at a rate of 5°C / min, reacted for 30 minutes, then heated to 1300°C at a rate of 3°C / min, reacted for 3 hours, then quenched at 1000°C for 1 hour, and then cooled to 25°C at a cooling rate of 3°C / min.
[0084] The molar ratio of the calcium-based material, the titanium-based material, the praseodymium-based material, the M-based material and the N-based material in the mixed solution is 1:1:0.5%:0.5:0.6.
[0085] The calcium-based material is calcium nitrate tetrahydrate, the titanium-based material is tetrabutyl titanate, the praseodymium-based material is praseodymium acetate, the M-based material is strontium acetate, and the N-based material is yttrium acetate.
[0086] Performance Evaluation
[0087] (1) Grain size test: The grain size of the long afterglow luminescent material in Example 1 was tested by scanning electron microscopy (EM-30+, COXEM, South Korea), and the average grain size was 1.4 μm.
[0088] (2) Luminescent color test: The luminescent color test of Example 1 was carried out. Under visible light, the long afterglow luminescent material was a light yellow powder. After being irradiated with an ultraviolet lamp for 5 minutes and placed in the dark, it showed bright red light (the excitation wavelength of the ultraviolet lamp was 365nm). After the long afterglow luminescent material of Example 1 was dispersed in deionized water and soaked for 10 days, it still showed bright red light under the ultraviolet lamp, and the luminescent effect did not change, which proved that the material had excellent water resistance and a wide range of applications.
[0089] (3) Afterglow time test: The long afterglow materials obtained in Examples 1-3 and Comparative Examples 1-4 were subjected to afterglow time test. A PR-305 long afterglow fluorescence tester produced by Zhejiang University Tricolor Instrument Co., Ltd. was used. During the test, the simulated sunlight with an excitation light intensity of 1000 lx was selected for continuous excitation for 20 minutes. After the excitation was completed, the afterglow brightness was recorded to decay to 0.00032 cd / m 2 The time required is the afterglow time of the material.
[0090] Table 1
[0091] Test items Afterglow time (h) Example 1 8.5 Example 2 8.3 Example 3 8.0 Comparative Example 1 0 Comparative Example 2 4.2 Comparative Example 3 3.0 Comparative Example 4 4.5
Claims
1. A long afterglow luminescent material, characterized in that: The chemical formula of the long afterglow luminescent material is CaM x N y TiO3Pr; In the chemical formula of the long afterglow luminescent material, M is Sr, N is Yb, In the above formula, 0.1≤x<0.3, 0.1≤y<0.
3.
2. A method for preparing a long afterglow luminescent material according to claim 1, characterized in that: The steps include: (1) Ingredients: Mixing a calcium-based material, a titanium-based material, a praseodymium-based material, an M-based material, an N-based material, water and anhydrous ethanol to obtain a mixed solution; (2) Drying and grinding: drying the mixed solution to obtain calcium titanate-doped rare earth solid, and grinding the solid to obtain calcium titanate-doped rare earth powder; (3) High temperature sintering: Calcium titanate doped rare earth powder is sintered at high temperature, quenched, and then cooled to room temperature.
3. The method for preparing a long afterglow luminescent material according to claim 2, characterized in that: The molar ratio of the calcium-based material, the titanium-based material, the praseodymium-based material, the M-based material and the N-based material in the mixed solution is 1:1: (0.3%-1.4%): (0.1-0.3): (0.1-0.3).
4. The method for preparing a long afterglow luminescent material according to claim 3, characterized in that: The calcium-based material is selected from at least one of calcium chloride, calcium chlorate, calcium gluconate, calcium bicarbonate, calcium nitrate, calcium nitrate tetrahydrate, and calcium chloride hexahydrate; the titanium-based material is selected from at least one of tetrabutyl titanate, titanium tetrachloride, and titanyl sulfate; the praseodymium-based material is at least one of praseodymium nitrate, praseodymium chloride, and praseodymium acetate; the M-based material is acetate and / or nitrate; and the N-based material is acetate and / or nitrate.
5. The method for preparing a long afterglow luminescent material according to claim 4, characterized in that: The drying temperature in step 2 is 60-90° C. and the drying time is 30-40 hours.
6. The method for preparing a long afterglow luminescent material according to claim 4, characterized in that: The specific steps of high temperature sintering in step 3 are: first heating the calcium titanate-doped rare earth powder from 20-30°C to 400-600°C at a rate of 3-6°C / min, reacting for 20-40min, then heating to 1100-1500°C at a rate of 2-5°C / min, and reacting for 2-5h.
7. The method for preparing a long afterglow luminescent material according to claim 4, characterized in that: The specific cooling step in step 3 is: cooling to 20-30°C at a cooling rate of 2-5°C / min.
8. An application of the long afterglow luminescent material according to claim 1, which is applied to road markings, tunnel inner walls, bridge guardrails, crash barriers, and traffic signs.
Citation Information
Patent Citations
Red long-afterglow phosphor and preparation method thereof
CN105647532A
Red long afterglow luminescent material and its prepn
CN1810921A
Red long afterglow luminescent material with high brightness and preparation method thereof
CN101693833A
Red high-brightness elastic stress luminescent material and preparation method thereof
CN103468258A
Sol-gel method for preparing praseodymium and metal co-doped calcium titanate fluorescent materials by double chelating agents
CN107312530A